On-the-Job Training : Returns, Barriers to Provision, and Policy Implications - Saraf, Priyam (World Bank, Washington, DC, 2017)
Firms that provide on-the-job training do so when it is critical to their productivity—and when productivity is critical to their survival. This paper begins by confirming a significant and positive return from on-the-job training on wages and productivity, as well as the presence of positive externalities from on-the-job training, while discussing the methodological considerations at play. The paper then reviews and validates the presence of market failures such as information asymmetries within the firm as a result of low-quality management practices that dampen firm demand for on-the-job training. Lack of competition in the firm's external environment appears to undermine adoption of on-the-job training and other complementary productivity-enhancing activities within the firm. The literature suggests that for most firms, a comprehensive policy approach that resolves external constraints to becoming more productive is likely to have a positive impact on the provision of on-the-job training and adoption of complementary policies. More direct forms of firm-level support to improve management capabilities could also alleviate under-provision of on-the-job training. Where societies have improved welfare as a goal, public policy measures would be needed to complement on-the-job training for some specific groups of workers (older, less educated, women). In essence, the paper highlights the importance of demand-side constraints for firms, rather than supply-side constraints, for the provision of on-the-job training.